TREATING CARDIOVASCULAR ATHEROSCLEROTIC PLAQUES WITH TONGMAIJIANGZHI (TMJZ) CAPSULE - Ren, Hong-Qiang; Zhao, Li; Zhang, Zhong Shuang; Wang, Zhong; Wang, Li; Duan, Jun Cang; Li, Li; Zhai, Zhi Hong; Qu, De Tao; Huang, Hui (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Atherosclerotic plaques can cause serious syndromes and mortality. Cholesterol accumulation in the plaques can disrupt the arterial flow, with lumen narrowing and stenosis, which contributes to heart attack and sudden cardiac death. The pharmacological treatment to atherosclerotic plaques can be anti-hypertensives, anti-cholesterol, and cleaning of the existed plaques. This work examined the effects of pharmacological Tongmaijiangzhi (TMJZ) capsule on atherosclerotic plaques. The radiological findings of the atherosclerotic plaques of 107 patients receiving TMJZ treatment were analyzed. We found that the TMJZ administration decreases plaque volume and alters the composition in a relatively short period, showing highly promising effects. TMJZ treatment is able to remove the existed atherosclerotic plaques with no side effects observed.